Multifunctional hydrogel coating modified magnesium alloy as well as preparation method and application thereof
By modifying the surface of magnesium alloy with a multifunctional hydrogel coating, the problem of rapid degradation and poor biocompatibility of magnesium alloy in the body is solved, its corrosion resistance and anticoagulant properties are significantly improved, and it promotes the growth of cells in the body. Growth and endothelial cell repair.
Patent Information
- Application Number
- CN202411428667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
AI Technical Summary
Magnesium alloys degrade rapidly in vivo and have poor biocompatibility, resulting in problems with anticoagulation performance and delayed endothelialization process in medical clinical applications.
By modifying the multi -functional hydrogel coating on the surface of the magnesium alloy, the polydopamine coating is formed with the self -gathering and clustering reactions of dopamine and acrylamide, and the biochemical or heparin or heparin or heparin is used through the double -key light polymerization reaction and the amide reaction. And selenium cosmnamine, forming anticoagulant functional hydrogel coating.
It significantly improves the corrosion resistance and biocompatibility of magnesium alloy, enhances its anticoagulant performance, and promotes cell growth and endothelial cell repair in the body.
Smart Images

Figure CN119345487A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to a magnesium alloy modified with a multifunctional hydrogel coating and a preparation method and application thereof. Background Art
[0002] Medical magnesium alloys have good biodegradability and mechanical properties and are ideal materials for the preparation of new degradable vascular stents. However, magnesium alloys have the problems of rapid degradation in the body and poor biocompatibility, which seriously restricts their application in clinical medicine.
[0003] Studies have shown that the corrosion products released by the rapid degradation of magnesium alloys and the lack of biological activity on the surface have a very important impact on the anti-coagulation properties of magnesium alloy materials and the endothelialization process of the magnesium alloy surface. Although there are studies on the use of surface chemical treatment, electrochemical treatment, etc., to set various inorganic non-metallic coatings, organic polymer coatings, and organic-inorganic composite coatings and other functional modification layers on the surface of magnesium alloys, to a certain extent, the degradation rate of magnesium alloy biomaterials in the body is reduced and its biocompatibility in the body is increased, however, the above functional modification layers have poor bonding with magnesium alloys, and the coatings are prone to fall off during application. After implantation, magnesium alloy materials are still prone to coagulation and delayed surface endothelialization, making it difficult to adapt to the physiological and pathological processes in the body, which is not conducive to the clinical application of the materials. Summary of the invention
[0004] The problem in the prior art is that magnesium alloys have poor corrosion resistance and are easily degraded rapidly in the body. To address the above problems, the present invention provides a magnesium alloy modified with a multifunctional hydrogel coating, which comprises the following steps:
[0005] (1) cleaning and drying the surface of the magnesium alloy to obtain Mg-OH;
[0006] (2) Dopamine and acrylamide are used as reaction monomers, dopamine undergoes self-polymerization reaction on the Mg-OH surface, and dopamine and acrylamide undergo copolymerization reaction on the Mg-OH surface, and finally a polydopamine coating containing double bonds is obtained on the Mg-OH surface;
[0007] (3) The amphiphilic compound containing double bonds and acrylamide both undergo double bond photopolymerization reaction on the surface of the polydopamine coating, and the surface of the polydopamine coating is modified to obtain a hydrogel coating;
[0008] (4) grafting bivalirudin or heparin onto the surface of the hydrogel coating through an amidation reaction (reaction of the carboxyl group in bivalirudin or heparin with the amino group on the surface of the hydrogel coating) to obtain an anticoagulant functionalized hydrogel coating;
[0009] (5) Through an amidation reaction (reaction of the amino group in selenocystamine dihydrochloride with the carboxyl group in the structure of bivalirudin or heparin), selenocystamine is grafted onto the surface of the anticoagulant functionalized hydrogel coating to obtain a multifunctional hydrogel coating.
[0010] Preferably, the cleaning method in step (1) comprises the following steps:
[0011] The surface of the magnesium alloy is first polished and cleaned, and then immersed in a NaOH aqueous solution with a temperature of 50-80° C. and a concentration of 1-10 M for 4-24 hours.
[0012] Preferably, the method of step (2) specifically comprises the following steps:
[0013] Immerse Mg-OH in a mixed solution formed by dopamine-Tris buffer solution and acrylamide-Tris buffer solution, adjust the pH of the mixed solution to 8-9, and react at room temperature for 8-10 hours. After the reaction is completed, wash and dry;
[0014] The mass concentrations of the dopamine-Tris buffer solution and the acrylamide-Tris buffer solution are both 1-4 mg / mL, and the mass ratio of dopamine to acrylamide in the mixed solution is 2:1.
[0015] Preferably, the preparation method of dopamine-Tris buffer solution is as follows:
[0016] Weigh dopamine and add it to a Tris buffer solution (molar concentration is 1 mol / L) with a pH of 8-9, and stir and mix evenly at room temperature to obtain a mass concentration of 2 mg / mL of dopamine in the Tris buffer solution (molar concentration is 1 mol / L).
[0017] Preferably, the preparation method of acrylamide-Tris buffer solution is as follows:
[0018] Weigh acrylamide and add it to a Tris buffer solution (molar concentration is 1 mol / L) with a pH of 8-9, and stir and mix evenly at room temperature to obtain a mass concentration of 2 mg / mL of acrylamide in the Tris buffer solution (molar concentration is 1 mol / L).
[0019] Preferably, the amphiphilic compound comprises one or a combination of two or more of 2-methacryloyloxyethyl phosphorylcholine, methacryloylethyl sulfobetaine (SBMA) and methacryloylethyl carboxybetaine.
[0020] Preferably, in step (3), the mass ratio of the amphiphilic compound containing a double bond to acrylamide is 1:2.
[0021] Preferably, the method of step (3) comprises the following steps:
[0022] The amphiphilic compound solution containing double bonds and the acrylamide solution are uniformly mixed to obtain a mixed solution, wherein the mass ratio of the amphiphilic compound containing double bonds to acrylamide in the mixed solution is 1:2, the mass concentration of the amphiphilic compound solution containing double bonds is 1-10%, and the mass concentration of the acrylamide solution is 1-10%. The mixed solution is uniformly dropped onto the surface of the magnesium alloy obtained in step (2), and then placed under ultraviolet light for illumination. After the illumination is completed, the surface of the polydopamine coating is modified to obtain a hydrogel coating.
[0023] Preferably, the preparation method of the amphiphilic compound solution containing double bonds is as follows:
[0024] The amphiphilic compound containing double bonds is dissolved in an aqueous solution, wherein the mass concentration of the amphiphilic compound containing double bonds in the aqueous solution is 1-10%.
[0025] Preferably, the preparation method of acrylamide solution is as follows:
[0026] Acrylamide is dissolved in an aqueous solution, wherein the mass concentration of the acrylamide in the solvent is 1-10%.
[0027] Preferably, the method of step (4) comprises the following steps:
[0028] The material obtained in step (3) is immersed in 10-30 mL of a bivalirudin solution or a heparin solution with a mass concentration of 1-5 mg / mL, 0.02-0.30 g of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 0.01-0.1 g of NHS (N-hydroxysuccinimide) are added, and the reaction is oscillated at room temperature for 2-8 hours. After the reaction is completed, the anti-coagulation functionalized hydrogel coating is obtained after washing with deionized water and drying.
[0029] Preferably, the preparation method of the bivalirudin solution is as follows: dissolve bivalirudin in 0.1 M phosphate buffer (pH 7.4), and the concentration of bivalirudin is 1-5 mg / mL.
[0030] Preferably, the heparin solution is prepared as follows: heparin is dissolved in 0.1 M phosphate buffer (pH=7.4, and the concentration of heparin is 1-5 mg / mL.
[0031] Preferably, the method of step (5) comprises the following steps:
[0032] The magnesium alloy obtained in step (4) is immersed in 10-30 mL of a selenocystamine dihydrochloride solution having a mass concentration of 1-5 mg / mL, 0.02-0.30 g of EDC and 0.01-0.1 g of NHS are added, and the reaction is oscillated at room temperature for 2-8 hours. After washing and drying, a multifunctional hydrogel coating is obtained.
[0033] The present invention has the following beneficial effects:
[0034] (1) In the present invention, a polydopamine coating is obtained on the surface of the magnesium alloy by self-polymerization of dopamine on the surface of the magnesium alloy and copolymerization of dopamine and acrylamide on the surface of the magnesium alloy. The polydopamine coating can significantly improve the corrosion resistance of the magnesium alloy.
[0035] (2) The amphiphilic compound containing double bonds and acrylamide are respectively photopolymerized with the double bonds on the surface of the polydopamine coating to be grafted on the surface of the polydopamine coating to obtain a hydrogel coating. The hydrogel coating imparts good hydrophilicity to the magnesium alloy. The surface-modified magnesium alloy has better biocompatibility and can better adapt to the cell growth environment in the body. At the same time, as the thickness of the coating increases, the corrosion resistance of the magnesium alloy is further improved.
[0036] (3) The surface of the multifunctional hydrogel coating obtained by the present invention is also grafted with bivalirudin and selenocystamine with anticoagulant function, which further enhances the anticoagulant performance of the magnesium alloy. Selenocystamine has glutathione peroxidase activity, which can catalyze the release of NO gas signal molecules from NO donors in the body, induce in situ repair and regeneration of vascular endothelium, and further enhance the anticoagulant performance and biocompatibility of the magnesium alloy.
[0037] (4) The method of chemically modifying the surface of magnesium alloys according to the present invention can be applied to the surfaces of almost all biomaterials and implantable medical devices. It has fast preparation speed, adjustable performance, and is easy to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 : This is a graph showing the water contact angle test results of Mg, Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV and Mg-NO in Example 1.
[0039] Figure 2 : These are the potentiodynamic scanning polarization curves and EIS diagrams of Mg, Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV and Mg-NO in Example 1.
[0040] Figure 3 : This is a comparative test diagram of the catalytic release of NO by Mg and Mg-NO in Example 1.
[0041] Figure 4 : This is a scanning electron microscope result of the platelet adhesion test of Mg, Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV and Mg-NO in Example 1.
[0042] Figure 5 : are the cell adhesion test results of Mg, Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV and Mg-NO in Example 1.
[0043] Figure 6 : These are the test results of cell proliferation of Mg, Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV and Mg-NO in Example 1.
[0044] Figure 7 : It is a comparison chart of the test results of the potentiodynamic scanning polarization curves of Mg-SA-1, Mg-SA-2 and Mg-SBMA / 2AAM in the present invention. DETAILED DESCRIPTION
[0045] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0046] The preparation method of dopamine-Tris buffer solution in step (2) of Example 1 is as follows:
[0047] Dopamine was weighed and added to a Tris buffer solution (molar concentration of 1 mol / L) at pH = 8.5, and stirred and mixed uniformly at room temperature, so that the mass concentration of dopamine in the Tris buffer solution (molar concentration of 1 mol / L) was 2 mg / mL.
[0048] The preparation method of the acrylamide-Tris buffer solution in step (2) of Example 1 is as follows:
[0049] Weigh acrylamide and add it to a Tris buffer solution (molar concentration is 1 mol / L) with a pH of 8.5, and stir and mix evenly at room temperature to obtain a mass concentration of 2 mg / mL of acrylamide in the Tris buffer solution (molar concentration is 1 mol / L).
[0050] The preparation method of the SBMA solution in step (3) of Example 1 is as follows:
[0051] SBMA was dissolved in deionized water to obtain a SBMA solution with a mass concentration of 5%.
[0052] The preparation method of the acrylamide solution in step (3) of Example 1 is as follows:
[0053] Acrylamide was dissolved in deionized water to obtain an acrylamide solution with a mass concentration of 10%.
[0054] The preparation method of the bivalirudin solution in step (4) of Example 1 is as follows:
[0055] Bivalirudin was dissolved in a phosphate buffer with a molar concentration of 0.1 M and a pH of 7.4 to obtain a bivalirudin solution with a mass concentration of 3 mg / mL.
[0056] The preparation method of selenocystamine dihydrochloride solution in step (5) of Example 1 is as follows:
[0057] Dissolve selenocystamine dihydrochloride in deionized water to obtain a selenocystamine dihydrochloride solution with a mass concentration of 3 mg / mL.
[0058] Example 1
[0059] A magnesium alloy modified with a multifunctional hydrogel coating, the preparation method is as follows:
[0060] (1) A 12 mm diameter and 5 mm thick AZ31B magnesium alloy disc (denoted as Mg) was polished and cleaned, then placed in a 3 M NaOH aqueous solution, immersed at 75° C. for 24 h, and then cleaned and dried to obtain Mg-OH;
[0061] (2) soaking the Mg-OH obtained in step (1) in a mixed solution formed by a dopamine-Tris buffer solution with a mass concentration of 2 mg / mL and an acrylamide-Tris buffer solution with a mass concentration of 2 mg / mL, wherein the volume ratio of the dopamine-Tris buffer solution to the acrylamide-Tris buffer solution is 2:1, adjusting the solution pH to 8.5, and oscillating the reaction at room temperature for 8 hours, and then washing with deionized water and drying to obtain Mg-DAM;
[0062] (3) After fully mixing 100 μL of 5 wt% SBMA solution and 100 μL of 10 wt% acrylamide solution, the mixture was evenly dropped onto the surface of Mg-DAM, and then irradiated under a 357.8 W UV lamp for 8 min, and then washed with deionized water and dried to obtain Mg-SBMA / 2AAM;
[0063] (4) Mg-SBMA / 2AAM was immersed in 20 mL of 3 mg / mL bivalirudin solution, and then 0.14 g EDC and 0.05 g NHS were added to the reaction system, and the reaction was oscillated at room temperature for 4 h. Then, Mg-BV was obtained after washing with deionized water and drying.
[0064] (5) Mg-BV was immersed in 20 mL of 3 mg / mL selenocystamine dihydrochloride solution, and then 0.14 g EDC and 0.05 g NHS were added to the reaction system. Then, the reaction was oscillated at room temperature for 4 h. After washing and drying, Mg-NO was obtained, which was a magnesium alloy modified with a multifunctional hydrogel coating.
[0065] Comparative Example 1 is the same as Example 1, except that in step (3) of Comparative Example 1, the mass concentration of the SBMA solution is 10%, and the mass concentration of the acrylamide solution is 5% (the mass ratio of SBMA to acrylamide is 2:1). The magnesium alloy obtained in Comparative Example 1 is recorded as Mg-SA-1.
[0066] Comparative Example 2 is the same as Example 1, except that in step (3) of Comparative Example 2, the mass concentration of the SBMA solution is 10% (the mass ratio of SBMA to acrylamide is 1:1), and the magnesium alloy obtained in Comparative Example 2 is recorded as Mg-SA-2.
[0067] Performance Testing
[0068] (1) Water contact angle measurement: The water contact angle meter (KrüSS GmbH, Germany) was used for measurement. During the measurement, 10 μL of deionized water was added to the surface of the material. After 10 seconds, the instrument automatically measured the contact angle. The measurement was carried out at room temperature.
[0069] The water contact angles of Mg without any surface treatment and Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV, Mg-NO, Mg-NO-1 and Mg-NO-2 obtained in the present invention were tested respectively. The specific test results are shown in the attached specification. Figure 1 As shown in the image, Mg-NO has the best hydrophilicity, and the order of contact angle is: Mg>Mg-OH>Mg-DAM>Mg-SBMA / 2AAM>Mg-BV>Mg-NO. In addition, the contact angle of Mg-NO is 11°, the water contact angle of Mg-SA-1 is 17.7°, and the water contact angle of Mg-SA-2 is 19.4°.
[0070] (2) The corrosion resistance was evaluated by potentiodynamic scanning polarization and electrochemical impedance spectroscopy. The specific test methods are as follows:
[0071] A standard three-electrode system (sample as working electrode, platinum wire as auxiliary electrode, and saturated calomel as reference electrode) was used to measure the potentiodynamic scanning polarization curves and electrochemical impedance spectroscopy (EIS) of the samples on a CHi660D electrochemical workstation (CHI Instruments, Inc, Shanghai, China) to characterize the electrochemical corrosion behavior of different modified materials.
[0072] The test solution is SBF simulated human body fluid (specific formula: NaCl 8g / L; KCl 0.4g / L; NaHCO 3 0.35g / L; CaCl 2 0.14g / L; Na 2 HPO 4 0.06g / L; KH 2 PO 4 0.06g / L; MgSO 4 7H 2 O 0.01g / L; glucose 1g / L; pH 7.4, solvent is deionized water), the scanning rate of the dynamic potentiodynamic polarization curve is 1mV / s. The corrosion potential (Ecorr) and corrosion current density (Icorr) of the sample are obtained according to the Tafel extrapolation method, and according to the corrosion current density data, the formula P i =22.85i corr (Reference Vacuum 110 (2014) 127-135.) Calculate the annual corrosion depth of magnesium alloy, where P i is the annual corrosion depth, i corr is the corrosion current density.
[0073] The AC impedance spectrum was measured by scanning a sinusoidal alternating current with an amplitude of 10 mV from high frequency to low frequency (100000-0.01 Hz).
[0074] The potential scanning polarization curve and EIS diagram obtained by the test are as shown in the attached manual. Figure 2 As shown in the figure, the unmodified magnesium alloy is very prone to corrosion in a physiological environment due to its active chemical properties, so its Ecorr is the lowest (-1.47V) and has the smallest capacitance ring size, indicating that the unmodified magnesium alloy has the greatest corrosion tendency. Its Icorr (1.31×10 -5 A.cm -2 ) is the largest, indicating that its corrosion rate is the fastest and its corrosion resistance is the worst. The image shows that Mg and Mg-OH, Mg-DAM, Mg-SBMA / 2AAM, Mg-BV, and Mg-NO obtained in the present invention are arranged in the order of being most susceptible to corrosion: Mg>Mg-OH>Mg-DAM>Mg-SBMA / 2AAM>Mg-BV>Mg-NO, and Mg-NO and Mg-SA-1 and Mg-SA-2 are arranged in the order of being most susceptible to corrosion: Mg-SA-1>Mg-SA-2>Mg-SBMA / 2AAM (see the attached manual) Figure 7It can be seen that when the ratio of SBMA to acrylamide is 1:2, the corrosion potential is the lowest and the corrosion current is the smallest, indicating that the corrosion resistance of the material is the best. When the ratio of SBMA to acrylamide is 1:1 (such as Comparative Example 2 of the present invention) or 2:1 (such as Comparative Example 1 of the present invention), the corrosion potential is higher and the corrosion resistance is relatively poor.
[0075] (3) The performance test method for catalytic release of NO is as follows:
[0076] Mg and Mg-NO were placed in 3 mL of PBS solution containing S-nitrosoglutathione (GSNO, NO donor, 10 μM). The NO release behavior in the PBS solution was determined by the nitrate reductase method. At different times, 50 μL of PBS solution was taken out and 50 μL of Grignard reagent I and 50 μL of Grignard reagent II were added respectively. The absorbance values were measured at 540 nm, and the NO concentration in the solution at this time was calculated according to the standard curve. The test results are shown in the attached manual. Figure 3 As shown in the figure, the experimental results show that the unmodified magnesium alloy has almost no catalytic effect on the release of NO from the donor even with the addition of a reducing agent. However, due to the introduction of the catalyst selenocystamine on the surface of Mg-NO, Mg-NO has a certain ability to continuously produce NO even without the addition of any reducing agent. When a reducing agent is added (Mg-NO-C), the release of NO increases significantly.
[0077] (4) Anticoagulation test
[0078] Platelet adhesion was used to evaluate the anticoagulant properties of the material. The purchased human whole blood (medical blood) was centrifuged at a speed of 1500rpm / min for 10min to obtain platelet-rich plasma (PRP). 200μL PRP was evenly covered on the surface of the sample and incubated in an incubator at a temperature of 37°C for 2.5h. After washing each sample three times with PBS solution (pH=7.4, molar concentration is 0.1M), a 2.5% mass concentration of glutaraldehyde aqueous solution was dripped on the surface of each sample, fixed at 4°C for 3h, and the sample was washed with PBS solution. Then, the sample was gradient dehydrated with ethanol aqueous solution (50%, 50%, 75%, 90%, 100%) and treated in ethanol solutions of step concentrations for 15min respectively. After drying at room temperature, SEM was used to observe the number and morphology of platelet adhesion. The specific test results are attached to the instructions. Figure 4As shown, the image shows that a large number of platelets adhere to the surface of the unmodified magnesium alloy, presenting a large number of aggregation states and some platelets have pseudopodia. Since the SBMA / 2AAM hydrogel coating has excellent hydrophilicity and anti-biological contamination performance, the adhesion and activation of platelets on the surface of the Mg-SBMA / 2AAM sample are significantly reduced; on the basis of the SBMA / 2AAM hydrogel coating, the grafting of bivalirudin can further significantly inhibit the adhesion and activation of platelets; after further grafting of selenocystamine, the platelet adhesion and activation of Mg-NO are significantly reduced, especially in the case of catalytic release of NO, the anticoagulant performance of the material is further significantly improved, and the multifunctional hydrogel coating for catalytic release of NO prepared by the present invention has a significant anticoagulant effect. The Mg-NO sample was added to 200 μL of PBS buffer solution (pH=7.4, molar concentration is 0.1 M) containing the reducing agent GSH (glutathione, 10 μM) and the donor GSNO (S-nitrosoglutathione, 10 μM), and the sample was recorded as Mg-NO-C.
[0079] (5) Endothelial cell growth behavior
[0080] The present invention uses cell adhesion and cell proliferation to evaluate the growth behavior of endothelial cells on the surface of magnesium alloy materials.
[0081] Cell adhesion: Two samples of different magnesium alloy materials were taken and placed in a sterile 24-well culture plate. 0.5 mL of endothelial cell suspension (5 × 10 4 cells / mL) and 1.5 mL of cell culture medium (DMEM / F12). One portion of the same magnesium alloy material was incubated at 37°C and 5% CO 2 The other was cultured in an incubator at 37°C and 5% CO for 6 h. 2 Incubate in an incubator for 24 hours. After washing with physiological saline, add a 2.5% mass concentration of glutaraldehyde aqueous solution to each sample and fix it at 4°C for 3 hours. After washing again, stain with 100 μL of rhodamine-phosphate buffer solution and 100 μL of 4,6-diamidino-2-phenylindole-phosphate buffer solution for 20 minutes and 10 minutes respectively. Finally, observe the number and morphology of cells on the surface under light with an inverted fluorescence microscope (Carl Zeiss A2inverted). The preparation method of the rhodamine-phosphate buffer solution is as follows:
[0082] Rhodamine was dissolved in a phosphate buffer solution with a molar concentration of 10 μg / mL and a pH of 7.4 to obtain a rhodamine-phosphate buffer solution with a mass concentration of 10 μg / mL.
[0083] The preparation method of the 4,6-diamidino-2-phenylindole-phosphate buffer solution is as follows:
[0084] 4,6-diamidino-2-phenylindole was dissolved in a phosphate buffer solution with a molar concentration of 500 ng / mL and a pH of 7.4 to obtain a 4,6-diamidino-2-phenylindole-phosphate buffer solution with a mass concentration of 500 ng / mL.
[0085] Cell proliferation: CCK-8 was used to evaluate the proliferation of cells. Two samples of different magnesium alloy materials were taken, and endothelial cells (ECV304) were inoculated on the surface of the magnesium alloy materials. One sample of the same magnesium alloy material was incubated at 37°C and 5% CO. 2 The other was cultured in an incubator at 37°C and 5% CO for 6 h. 2 The samples were cultured in an incubator for 24 h, and then transferred to well plates, 0.5 ml of CCK-8 solution (10%, 10% fetal bovine serum in DMEM / F12 cell culture medium) was added, and cultured for 3.5 h at 37 ° C. Finally, 200 μL of culture medium was placed in a 96-well plate and the absorbance at 450 nm was measured.
[0086] The results of the cell adhesion test are as shown in the instructions. Figure 5 The test results of cell proliferation are shown in the attached manual. Figure 6 As shown, the images show that the adhesion and spreading of endothelial cells on the Mg-NO surface were significantly improved in the same period of time, and the cell growth was best under the catalytic release of NO. The Mg-NO sample was added to 200 μL of PBS buffer solution (pH = 7.4, molar concentration is 0.1 M) containing the reducing agent GSH (glutathione, 10 μM) and the donor GSNO (S-nitrosoglutathione, 10 μM), and the sample was recorded as Mg-NO-C.
[0087] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A magnesium alloy modified with a multifunctional hydrogel coating, characterized in that: The following steps are involved: (1) cleaning and drying the surface of the magnesium alloy to obtain Mg-OH; (2) Dopamine and acrylamide are used as reaction monomers, dopamine undergoes self-polymerization reaction on the Mg-OH surface, and dopamine and acrylamide undergo copolymerization reaction on the Mg-OH surface, and finally a polydopamine coating containing double bonds is obtained on the Mg-OH surface; (3) The amphiphilic compound containing double bonds and acrylamide both undergo double bond photopolymerization reaction on the surface of the polydopamine coating, and the surface of the polydopamine coating is modified to obtain a hydrogel coating; (4) grafting bivalirudin or heparin onto the surface of the hydrogel coating through an amidation reaction to obtain an anticoagulant functionalized hydrogel coating; (5) Through an amidation reaction, selenocystamine is grafted onto the surface of the anticoagulant functionalized hydrogel coating to obtain a multifunctional hydrogel coating.
2. A magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The cleaning method in step (1) comprises the following steps: The surface of the magnesium alloy is first polished and cleaned, and then immersed in a NaOH aqueous solution with a temperature of 50-80° C. and a concentration of 1-10 M for 4-24 hours.
3. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The method of step (2) specifically comprises the following steps: Immerse Mg-OH in a mixed solution formed by dopamine-Tris buffer solution and acrylamide-Tris buffer solution, adjust the pH of the mixed solution to 8-9, and react at room temperature for 8-10 hours. After the reaction is completed, wash and dry; The mass concentrations of the dopamine-Tris buffer solution and the acrylamide-Tris buffer solution are both 1-4 mg / mL, and the mass ratio of dopamine to acrylamide in the mixed solution is 2:
1.
4. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The amphiphilic compound includes one or a combination of two or more of 2-methacryloyloxyethyl phosphorylcholine, methacryloylethyl sulfobetaine and methacryloylethyl carboxybetaine.
5. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: In step (3), the mass ratio of the amphiphilic compound containing a double bond to acrylamide is 1:
2.
6. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The method of step (3) comprises the following steps: The amphiphilic compound solution containing double bonds and the acrylamide solution are uniformly mixed to obtain a mixed solution, wherein the mass ratio of the amphiphilic compound containing double bonds to acrylamide in the mixed solution is 1:2, the mass concentration of the amphiphilic compound solution containing double bonds is 1-10%, and the mass concentration of the acrylamide solution is 1-10%. The mixed solution is uniformly dropped onto the surface of the magnesium alloy obtained in step (2), and then the reaction system is placed under ultraviolet light for illumination. After the illumination is completed, the surface of the polydopamine coating is modified to obtain a hydrogel coating.
7. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The method of step (4) comprises the following steps: The material obtained in step (3) is immersed in 10-30 mL of a bivalirudin solution or a heparin solution with a mass concentration of 1-5 mg / mL, 0.02-0.30 g of EDC and 0.01-0.1 g of NHS are added, and the reaction is oscillated at room temperature for 2-8 hours. After the reaction is completed, the anticoagulant functionalized hydrogel coating is obtained after washing with deionized water.
8. The magnesium alloy modified with a multifunctional hydrogel coating according to claim 1, characterized in that: The method of step (5) comprises the following steps: The magnesium alloy obtained in step (4) is immersed in 10-30 mL of a selenocystamine dihydrochloride solution having a mass concentration of 1-5 mg / mL, 0.02-0.30 g of EDC and 0.01-0.1 g of NHS are added, and the reaction is oscillated at room temperature for 2-8 hours. After washing and drying, a multifunctional hydrogel coating is obtained.
9. A magnesium alloy modified with a multifunctional hydrogel coating according to any one of claims 1 to 8, characterized in that: Can be used as degradable vascular stent material.